The dynamics of single-to-multi layer transition in bacterial swarms - Grobas, Iago; Asally, Munehiro; Polin, Marco (Frontiers in Soft Matter, 2022)
Wet self-propelled rods at high densities can exhibit a state of mesoscale turbulence: a disordered lattice of vortices with chaotic dynamics and a characteristic length scale. Such a state is commonly studied by a two-dimensional continuum model. However, less is known about the dynamic behaviour of self-propelled rods in three- or quasi-two- dimensions, which can be found in biological systems, for example, during the formation of bacterial aggregates and biolms. In this study, we characterised the formation of multi-layered islands in a monolayer of swarming cells using the rod-shaped bacteria B. subtilis as a model system. We focused on understanding how bacteria form multiple layers and how the presence of stress aects the multiple layer formation. Following our previous study where we reported that the initiation of the multilayer formation can be accounted by the framework of motility-induced phase separation (MIPS), this study analysed how this phase separation is impacted by the presence of stress, specially under the exposure to a gradient of antibiotic. The analyses show that in the presence of an antibiotic gradient, the multi-layer formation happens by a nucleation and growth of well-defined multilayered clusters instead of by the uncontrolled emergence of the multilayer, resembling the traditional thermodynamic processes of binodal and spinodal decomposition respectively. Finally, the multilayer gives place to waves of bacteria that can travel towards high concentrations of antibiotics and that resemble travelling waves predicted by simulations of mixtures of passive and active particles.